Strengthening and drying rate of a drying emulsion layer. Issue 42 (16th October 2018) - Goavec, M.; Rodts, S.; Gaudefroy, V.; Coquil, M.; Keita, E.; Goyon, J.; Chateau, X.; Coussot, P.
Abstract : Silicone in water emulsion at different stages of drying (decreasing water concentration) viewed from the side (top) and from above (bottom) in a Petri dish, showing the formation of oil and surfactant layers below and around the free surface. Abstract : From direct observations and MRI measurements we demonstrate that during the drying of a direct (oil in water) emulsion the whole system essentially concentrates homogeneously, which leads to shrinkage, without air penetration. The structure and mechanical strength ( i.e. the elastic modulus) of this concentrated bulk are not significantly different from those of an emulsion directly prepared at this higher concentration. Despite this phenomenon, the drying rate continuously and rapidly decreases as the water content decreases, in contrast with the drying of a simple granular packing. This results from a concentration gradient which develops towards the free surface of the sample where the oil droplets finally coalesce, ultimately forming an oil layer covering the sample through which the water molecules have to diffuse before evaporating. Moreover, as during the process, the liquid is transported towards the free surface where it evaporates, surfactants accumulate and tend to form a thin solid layer below the oil layer, which tends to further reduce the drying rate.